Lumbopelvic Movement Pattern Differences in Two Groups of Low Back Pain Subjects with and without Rotational Activities during Active Hip External Rotation Test - Meissam Sadeghisani; Mohammad Jafar Shaterzadeh; Mohammad Taghi karimi; Ahmad Reza Rafiei (Vesnu Publications, 2014)
Introduction: The aim of this study was to compare the lumbopelvic movement pattern between two groups of low back pain patients with and without rotational demand activity during active hip external rotation test. Materials and methods: Thirty nine male subjects with non-specific chronic low back pain were participated in this study. They were included fifteen subjects (mean age=31.5 years) with rotational demand activities such as tennis, squash and twenty four subjects (mean age=31.2 years) without rotational demand activities. Kinematic data from lumbopelvic-hip region during active hip external rotation test was collected by 3-D motion analysis system. Variables including ROM of hip external rotation, lower extremity external rotation, pelvic rotation, and pelvic rotation during first half of hip rotation and timing of pelvic and hip movement were calculated by MATHLAB and after this; independent T-test was used to compare the same variables between two groups of study. Results: Lumbopelvic rotation in individuals with rotational demand activity was significantly more than other group (p=0/03). But other variables between two groups were not prominently different (p>0/05). Conclusion: Lumbopelvic movement pattern in subjects with low back pain is mainly different in comparison with other group. Key words: Low back pain, lumbopelvic motion, task specific, movement impairment, hip external rotation